EVALUATION AND OPTIMIZATION OF ANTIOXIDANT POTENTIALITY OF XYLARIA FEEJEENSIS HMJAU22039 - Rebbapragada, Durga; Kalyanaraman, Rajagopal (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Antioxidants neutralize free radicals generated in the human body and prevent them from causing damage. The present study is aimed to evaluate and optimize the antioxidant activity of Xylaria feejeensis HMJAU22039 an endophyte isolated from Tectona grandis. Methods: The antioxidant potential was measured by 1-1diphenyl-2-picryl-hydrazil (DPPH) radical scavenging assay and nitric oxide (NO) scavenging assay. Total phenolic content (TPC) of the samples was measured by Folinâ€“Ciocalteu reagent based assay, and the values were obtained from the regression equation: y = 0.006141x + 0.157733. Results: Potato dextrose yeast extract broth medium was selected as the basal medium as it reported a high antioxidant activity. The basal medium was optimized with 2% dextrose, 0.2% yeast extract, and 200 g/L potato infusion. Dextrose and yeast extract were selected as carbon and nitrogen sources, respectively, as they reported high antioxidant activity. The antioxidant activity and phenolic content are highest at static condition (18.14 mg/g). Incubation temperature of 30Â°C and pH of the initial medium at 6 were found to be optimum conditions for high antioxidant activity. An incubation period of 20 days reported the highest antioxidant activity and phenolic content. Methanol extract recorded high antioxidant activity with a DPPH (73.86%) followed by ethyl acetate and chloroform fractions. Conclusion: The study highlights the importance of different physiochemical parameters in the production of secondary metabolites having antioxidant properties. The results reveal a significant positive correlation between DPPH radical scavenging assay, NO scavenging assay, and TPC. Keywords: 1-1diphenyl-2-picryl-hydrazil, Total phenolic content, Endophytic fungus, Tectona grandis.